Aplikasi Terapi Guided Imagery Untuk Mengurangi Nyeri Akut Pada Ny. S Dengan Ca Mammae: Studi Kasus - Rr. Reza Fitri Dwi Milenia; Murtaqib Murtaqib; Ana Nistiandani; Sulis Setyowati (Jurnal Keperawatan Klinis dan Komunitas (Clinical and Community Nursing Journal), 2023)
Background: Breast cancer is the second leading cause of death in women after cervical cancer. One of the most feared symptoms by cancer patients is pain. Cancer patients have used guided imagery relaxation techniques for several years, and it has been proven that they can help reduce the side effects of chemotherapy, such as nausea, vomiting, pain, anxiety, and depression.Objective: To analyze the application of guided imagery therapy to reduce acute pain in Mrs.S with Ca Mammae in the Upper Melati Room, RSD dr. Soebandi.Case report: Mrs. S, 46 years old, is being treated in the Melati Room at RSD dr. Soebandi Jember with a medical diagnosis of Ca Mammae. When he came to RSD dr. Soebandi Jember patient complained of pain with a scale of 5 with a dull ache in the left breast. Patients were given the main intervention of Guided Imagery therapy for 3 days of treatment to reduce pain.Outcome: The patient said that on the first day of the intervention, the pain felt intermittent and it was difficult to sleep. Then after being given guided imagery therapy, the pain felt reduced.Conclusion: Guided imagery therapy can be applied to breast cancer patients where it can help reduce pain due to breast cancer felt by patients so that it will help in patient health care